Editorial [In Issue: Competence for Rural Innovation and Transformation] - Davis, Kristin E. (Taylor and Francis, 2022)
The Journal of Agricultural Education and Extension (JAEE) publishes authoritative and well-referenced scientific articles in the field of agricultural education and extension following a double-blind peer review process. This often takes two to three rounds of revisions and reviews. The editors-in-chief, Prof. Laurens Klerkx and Dr. Kristin Davis, are supported by editors with expertise in agricultural innovation and innovation systems; psychology, social learning; behaviour and intentions; extension programme design and evaluation; education methods, theory, and practice; quantitative and qualitative methodologies, information and communication technologies, and much more.